FDG‐PET IN HEALTHY AND EPILEPTIC LAGOTTO ROMAGNOLO DOGS AND CHANGES IN BRAIN GLUCOSE UPTAKE WITH AGE. Issue 3 (20th December 2013) - Jokinen, Tarja S.; Haaparanta‐Solin, Merja; Viitmaa, Ranno; Grönroos, Tove J.; Johansson, Jarkko; Bergamasco, Luciana; Snellman, Marjatta; Metsähonkala, Liisa
<x xml:space="preserve">Abstract</x> Regional cerebral metabolism and blood flow can be measured noninvasively with positron emission tomography (PET). 2‐[18F]fluoro‐2‐deoxy‐D‐glucose (FDG) widely serves as a PET tracer in human patients with epilepsy to identify the seizure focus. The goal of this prospective study was to determine whether juvenile or adult dogs with focal‐onset epilepsy exhibit abnormal cerebral glucose uptake interictally and whether glucose uptake changes with age. We used FDG‐PET to examine six Lagotto Romagnolo dogs with juvenile epilepsy, two dogs with adult‐onset epilepsy, and five control dogs of the same breed at different ages. Three researchers unaware of dog clinical status visually analyzed co‐registered PET and magnetic resonance imaging (MRI) images. Results of the visual PET analyses were compared with electroencephalography (EEG) results. In semiquantitative analysis, relative standard uptake values (SUV) of regions of interest (ROI) drawn to different brain regions were compared between epileptic and control dogs. Visual analysis revealed areas of hypometabolism interictally in five out of six dogs with juvenile epilepsy in the occipital, temporal, and parietal cortex. Changes in EEG occurred in three of these dogs in the same areas where PET showed cortical hypometabolism. Visual analysis showed no abnormalities in cerebral glucose uptake in dogs with adult‐onset epilepsy. Semiquantitative analysis detected no differences between epileptic and control dogs. This result emphasizes the importance of visual analysis in FDG‐PET studies of epileptic dogs. A change in glucose uptake was also detected with age. Glucose uptake values increased between dog ages of 8 and 28 weeks and then remained constant.